Sistemática das espécies de Ceroplastinae Atkinson, 1886 (Hemíptera: Coccoidea: Coccidae) que ocorrem no estado de São Paulo, Brasil e inventariação de seus parasitóides - Peronti, Ana Lúcia Benfatti Gonzalez (Universidade Federal de São Carlos, 2004)
The species of Ceroplastinae (Hemiptera: Coccoidea: Coccidae) from São Paulo state were revised and associated parasitoids were inventoried. Forty-three species of the Ceroplastinae were studied, 27 known species were redescribed and 6 new species described. Ceroplastes campinensis Hempel, 1901, C. bicolor Hempel, 1901, C. excaericae Hempel, 1912 and C. farmairii (Signoret, 1866) were not studied because the type material or other specimens were not found. Eight new synonym are established: Ceroplastes psidii (Chavannes, 1848) and C. simplex Hempel, 1900 with C. janeirensis; C. cultus Hempel, 1900, C. cuneatus Hempel, 1900, C. rarus Hempel, 1900 and C. rotundus Hempel, 1900 with C. cirripediformis; C. novaesi Hempel, 1900 with C. lucidus Hempel, 1900 and C. rhizophorae Hempel, 1918 with C. grandis Hempel, 1900. One new combination is proposed. Ceroplastes stellifer (Westwood, 1871). Ceroplastes flosculoides is recorded for the first time in Brazil and Ceroplastes cassiae (Chavannes, 1848), C. deodorensis Hempel, C. formosus Hempel and C. quadratus Green are recorded for the first time in São Paulo state. Ceroplastinae is now formed by 31 species, all included in Ceroplastes genus. In addition, synonym list, geographic distribution, lists of hosts and illustrations have been presented, together with a dichotomous key to the groups of the Ceroplastinae and a dichotomous key to species of the Ceroplastes group and another to species of the Ceroplastidia group from São Paulo state. Thirty-one Hymenoptera parasitoids distributed in 7 families of the Chalcidoidea in association with Ceroplastes species: Coccophagus Westwood sp1., C. sp2, C. sp3 (Aphelinidae); Anicetus sp., Coccidencyrtus sp., Encyrtus baezi (Brèthes, 1921), Metaphycus sp1, M. sp2, M. sp3, M. sp4, M. sp5, M. sp6, M. sp7, M. sp8. and Microterys sp. (Encyrtidae), Aprostocetus sp1., A. sp2 and A. sp3, Horismenus and Tetrastichinae sp. (Eulophidae), Brasema sp., Lecaniobius grandis (De Santis, 1950), L. utilis Compere, 1939 and L. cockerellii Ashmead, 1896 (Eupelmidae), Erotolepsia sp. and Cephaleta brasiliensis (De Santis, 1963) (Pteromalidae) and Signiphora sp1. S. sp2 and S. sp3 (Signiphoridae) were found. Every genus mentioned above, except Coccophagus, is associated with Ceroplastinae for the first time in Brazil. The first occurrence of both the genus Microterys and Encyrtus baezi for Brazil and genus Brasema and Brachymeria pedalis (Cresson, 1872) for the state of São Paulo is here recorded. A CD-ROM, including species of economic importance Ceroplastinae and associated parasitoids, is presented.
Keywords: Homoptero; Taxonomia; Interação inseto-planta; Parasitóide; Heminoptero; CIENCIAS BIOLOGICAS::ZOOLOGIA